Implementation of the Principles of Good Corporate Governance Through Internal Control of Savings and Loan Activities at Ksp Kopdit Megu Lekuk Hubin - Noventriana Klarisanti Da Luja; Wilhelmina Mitan; Paulus Libu Lamawitak (Neo Journal of economy and social humanities, 2024)
This study aims to evaluate the implementation of the principles of Good Corporate Governance (GCG) through internal control of savings and loan activities at KSP Kopdit Megu Lekuk Hubin. The methods used include interviews, observations, and document analysis to collect data. The results of the study show that the application of GCG principles, which include transparency, accountability, independence, responsibility, and justice, plays an important role in improving cooperative financial management. Although some principles have been implemented well, there are obstacles in the aspects of transparency and responsibility that have not been maximized. The author recommends improving the information technology system and training for administrators and members to optimize internal control and support the success of savings and loan activities. This research is expected to contribute to the development of cooperatives and increase understanding of GCG among cooperative members.